PENDIDIKAN KEIMANAN DAN PENDIDIKAN AKHLAK - Ahmad Rifa'i (Institut Agama Islam Darul Ulum Kandangan, 2020)
Faith formation should begin in the womb, in line with personality growth. It`s begin when marriage. Parents are take most important role in faith and moral education. The method of faith education is: recite qauliyah verses, learn the histories in the Qur`an as a modals, promises and threats (basyir wa nadzir), praying of Allah, habituation and discipline in doing good, indoctrination. Moral education methods are: imitation method, trial and error method (tried and wrong), conditioning method, problem solving method, targhib wa tarhib method, lecturing method, question and answer method, discussion method, demonstration method, amtsal method, drill method, uswah and qudwah method, observation method, social interaction method.